"Washington in Golry": Clerical Reflections on the Death of George Washington and the Making of a New Nation - Dragas, Marcus Gregory (Wake Forest University, 2009)
This thesis examines the eulogies delivered in honor of George Washington by Christian clerics between December of 1799 and February of 1800. These orations can be viewed as cultural performances that helped to strengthen the social and political order by fostering a sense of community that transcended local boundaries, bringing an entire nation together to mourn their fallen leader. By ruminating on a number of theological as well as political themes, clergymen across the country used their words to help shape the country’s collective identity, defining Americans as set apart by God, republican, and Christian. I argue that this attempt to shape America’s identity was, in part, a negotiation of collective fear that the relatively new American nation would fail. Chapter one examines the eulogists’ participation in the broader tradition of providential thought, casting Americans as having a special relationship with God. Chapter two looks at the clerics’ reflections on leadership in the new republic. Chapter three considers how these clerics used Washington’s death as a way of advocating the Christian religion. Throughout the thesis, I reflect on the idea of an American civil religion and the ways in which these eulogies participated in developing some of its tenets.
Keywords: Religion; American History